Predicting Recidivism Among Released Juvenile Offenders in Florida: an Evaluation of the Residential Positive Achievement Change Tool - Hay, Carter (Youth violence and juvenile justice, 2018)
Each year in the United States, as many as 100,000 juvenile offenders are released after completing a residential placement. A significant task for researchers is to identify the factors that explain variations in recidivism. This study considers this by evaluating the predictive validity of the Residential Positive Achievement Change Tool (R-PACT), a fourth-generation risk assessment instrument adopted by Florida for use in all of its juvenile residential facilities. The R-PACT includes a wide variety of static and dynamic risk and needs scales that are used here to predict reoffending among 4,700 released juvenile offenders in Florida. We devote special attention to (1) whether R-PACT scales typically predict reoffending and (2) whether the R-PACT’s predictive validity varies across different subgroups of offenders. In considering these questions, we also consider whether the predictive risk and protective factors in prior research are predictive in the R-PACT as well. The analysis revealed relatively strong support for the R-PACT, but there were nuanced exceptions to that pattern. We discuss the implications these findings have for assessing risk, monitoring progress among residential youth, and predicting reoffending.